2021
DOI: 10.1080/09524622.2021.1938226
|View full text |Cite
|
Sign up to set email alerts
|

A new putative species in the Ectatomma ruidum complex (Formicidae: Ectatomminae) produces a species-specific distress call

Abstract: Social insects communicate by using chemical, visual, tactile, and acoustic signals, including 19 stridulations. Ectatomma ruidum is a mainly Neotropical ant species complex that has faced 20 strong divergence at the genetic level; the species have a highly variable blend of cuticular 21 hydrocarbons and a relatively conserved morphology. Based on evidence for genetic and 22 chemical differentiation, we tested for variation in acoustic traits. We compared the 23 stridulations produced by the species E. ruidum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…We generated CHC profiles of 24 workers from two localities in Mexico (Puerto Morelos, Quintana Roo, 5 nests; Cuatode, Municipality of Santa María Tonameca, Oaxaca, 6 nests) following the procedure described by Peña‐Carrillo, Lorenzi, et al (2021), and pooled this information with the data set obtained in the latter study. The complete data set comprised 132 workers and included two to five ants per colony.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We generated CHC profiles of 24 workers from two localities in Mexico (Puerto Morelos, Quintana Roo, 5 nests; Cuatode, Municipality of Santa María Tonameca, Oaxaca, 6 nests) following the procedure described by Peña‐Carrillo, Lorenzi, et al (2021), and pooled this information with the data set obtained in the latter study. The complete data set comprised 132 workers and included two to five ants per colony.…”
Section: Methodsmentioning
confidence: 99%
“…The CHC profiles varied considerably among populations, supporting the existence of various evolutionary lineages within the complex. More recently, a study of the distress call for members of this complex found that a population in Huaxpaltepec, Oaxaca, Mexico, differs significantly in this trait from other examined populations, strongly suggesting that this population could represent a distinct, undescribed species (Peña‐Carrillo, Lorenzi, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The CHC profiles varied considerably among populations, supporting the existence of various evolutionary lineages within the complex. More recently, an acoustic study of the distress call for members of this complex found that a population in Huaxpaltepec, Oaxaca, Mexico, differs significantly in this trait from other examined populations, strongly suggesting that this population could represent a distinct, undescribed species (Peña-Carrillo et al 2021b).…”
Section: Introductionmentioning
confidence: 98%
“…These are Ectatomma ruidum sp. 1, 2, 3–4, 5 and a possible 2x3 hybrid [ 31 34 ]. In terms of habitat, this species complex is widely distributed, occupying agricultural systems, savannas, and forests from sea level to an altitude of 1500–1600 m [ 26 ] and up to 2200 m [ 35 ].…”
Section: Introductionmentioning
confidence: 99%